Representation of National Identity on the Net - M. R. Snegur (Дискурс, 2023)
Introduction. The purpose of the article is to study and construct the typology of situations of the  national  identity actualization  of young people  in the  digital space.  The scientific novelty of the work lies in the study of the constructing national identity process  as a result of the  assimilation  of institutional  nation-building, passed  through  the  filters of personal attitudes,  that can be observed  in the variability of representing national  identity ways in various social situations.  The relevance  is conditioned by modern socio-political conditions and the need for in-depth study of the category of national identity.Methodology and sources. The research methodology is based on the approaches of social constructivism (the nation as an “imaginary community” by B. Anderson), symbolic interactionism  (the dramatic approach of I. Goffmann), ethno-symbolism (everyday nationalism  of  J.  Hutchinson)  and  memory  studies  (cultural memory  of  J.  Assman). The research method is a discourse analysis of blogs in TikTok and Instagram, the unit of analysis is a blog as a case,  sample  size made  up 127  cases.  The collection  of empirical data took place from 01.26.2022 to 03.10.2022.Results and discussion. The digital space provides the conditions for the maximum degree of  intensity  of  the  national  identity representation, which can  be  represented in social networks  by  a  wide variety  of  forms  (costume,   text,  music,  image,  scenery,  etc.).  The following types of representation of national identity in the network have been  identified: national identity as a “profession”, as “fandom”, national identity in the context  of constant updating  (migrants,  intercultural  marriage),  in  the  context   of  everyday  life,  situational national identity, lack of a specific national identity.Conclusion. The conducted empirical research allows to construct the typology of situations of national identity of young people representations in the network. The typology is based on  the   degree   of  intensity  of  national   identity  representation.  The  typology  can  be represented as a continuum, on one pole of which there is a vivid representation of national identity, on the other - an active blurring and confusion of national markers.